Increasing the efficiency of using open wagons by improving vibration unloading machines - Повороженко, Євгеній Віталійович (Eastern-European Journal of Enterprise Technologies, 2014)
Scientific and practical problem of increasing the efficiency of unloading technology of bulk cargo from open wagons by improving unloading machines is solved in the paper. Based on the analysis of parameters that affect the operational efficiency of open wagons and comparison of existing technologies and technical means for unloading bulk cargo from open wagons it was found that technology with using overhead vibrating machines has become the most prevalent. However, these machines do not meet current production requirements concerning performance and preservation of rolling stock. Based on the slope stability theory, correlation between vibration body accelerations of the open wagon and its unloading duration is determined. New mathematical model of vibration unloading of open wagons taking into account the change in weight of cargo residues and finite-element model of the “open wagon -vibromachine – cargo” system, which allow at the design stage to assess its performance and examine its impact on the durability of open wagon body elements are developed. Rational values of driving force frequency are found, which promotes increasing the unloading efficiency of open wagons and ensures the preservation of open wagons. Experimental studies have shown the adequacy of theoretical research in practice. The practical recommendations, aimed at reducing the circulation of rolling stock by increasing the efficiency of vibration unloading of bulk cargoes from open wagons are proposed. The research results are implemented at the state-owned company “Vinnytsyatransprylad”.